Instrumentalisasi Hukum dan Ketahanan Demokrasi: Analisis Politik Hukum Mahfud MD dalam Perspektif Hukum Islam - Pamungkas, Ery; Hidayati, Maslihati Nur (Tasyri' : Journal of Islamic Law, 2025)
This article discusses the phenomenon of legal instrumentalization in Indonesian constitutional practice and its implications for democratic resilience, by highlighting the political thinking of Mahfud MD. Through the approach  of doctrinal legal research and normative analysis, this study found that the law is often used as an instrument of power by the dominant political configuration, thereby weakening the principles of judicial independence and constitutional supremacy. In this context, Mahfud MD's idea of responsive legal politics becomes relevant to uphold the law as a means of substantive justice, not just a tool of power legitimization. This study then relates this framework to the principles  of maqāṣid al-sharī'ah in Islamic law, especially in the aspects of the maintenance of justice (ḥifẓ al-'adl), reason (ḥifẓ al-'aql), and the public benefit (maṣlaḥah 'āmmah). The integration of the two shows that strengthening democracy requires a political reconstruction of the law based on Islamic ethical values, namely the balance between power, justice, and moral responsibility of state administrators. This study recommends the need for a national legal design that is oriented towards substantive justice and the protection of human rights as a form of application of maqāṣid al-sharī'ah in the democratic legal system in Indonesia.